Alcohol- and water-extracted soy protein concentrates for early-weaned pigs - L L Burnham; M R Cabrera; I H Kim; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 72 weanling pigs (average initial wt of 7 lb and 10 d of age) was used in a 38-d growth assay to determine the nutritional value of alcohol- and water-extracted soy protein concentrates. Pigs were sorted by sex, weight, and ancestry and assigned to 12 pens with six pigs/pen. The soy preparations were fed in a nursery regimen with Phase I (d 0 to 10), Phase II (d 10 to 24), and Phase III (d 24 to 38) diets. Pigs and feeders were weighed at initiation and conclusion of each phase, with fecal samples collected on d 38 for determination of OM and N digestibilities. Pigs fed the alcoholextracted soy protein concentrate had greater average daily gain (ADG) in all phases, with similar increases in average daily feed intake (ADFI) compared to pigs fed water-extracted soy protein concentrate. However, feed/gain (F/G) was similar throughout the experiment for pigs fed the soy protein treatments. The diets with water-extracted soy protein concentrate had greater digestibility of dry matter (OM) than the diets with the alcohol-extracted product, but N digestibility was similar for both treatments. Although water is an inexpensive solvent compared to alcohol, pigs fed the alcohol-extracted soy protein concentrate had improved growth performance compared to those fed the water-extracted product.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Alcohol extraction; Water extraction; Soy protein concentrate; Nursery pigs